Factor Affecting Startups in Kathmandu - Ghimire, Saroj (Nepalese Journal of Finance, 2025)
This study examines the factor affecting startups in Kathmandu. Growth rate of startup is the dependent variable. The selected independent variables are access to funding, regulatory environment, local market demand, entrepreneurial skills, and government support. The primary source of data is used to assess the opinions of respondents regarding access to funding, regulatory environment, local market demand, entrepreneurial skills, government support, and growth rate of startups. The study is based on the primary sources data of 130 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of factor affecting startup in Kathmandu. The study showed a positive impact of access to funding on growth rate of startup. It indicates that access to funding for startup leads to increase in growth rate of startup. Similarly, the study showed a positive impact of regulatory environment on growth rate of startup. It indicates that supportive regulatory environment leads to increase in growth rate of startup. Likewise, the study showed a positive impact of local market demand on growth rate of startup. It indicates that higher the demand from local market leads to increase in growth rate of startup. In addition, the study also showed a positive impact of entrepreneurial skills on growth rate of startup. It indicates that better entrepreneurial skills lead to increase in growth rate of startup. Further, the study showed a positive impact of government support on growth rate of startup. It indicates that higher the government support, higher would be the growth rate of startup.